Phosphate sorption parameters in relation to soil properties in some major agricultural soils of India (SAARC Journal of Agriculture, 2016)
Phosphorus sorption characteristics of some Indian representative agricultural soils belonging to four soil orders namely Vertisol, Inceptisol, Alfisol and Ultisol were investigated for adsorption behaviour of P and sorption data were fitted to Langmuir and Freundlich equations. The Langmuir constant i.e. adsorption maxima was highest for Vertisol (716.85 ?g g-1), followed by Ultisol (633.3 ?g g-1), Alfisol (501.46 ?g g-1) and Inceptisol (522.93 ?g g-1) respectively. The Freundlich k value for Vertisol, Inceptisol, Alfisol and Ultisol were 159.12, 59.41, 110.57 and 181.36 ?g g-1 respectively, whereas the n values were 2.05, 1.92, 2.49 and 3.07 g ml-1 respectively. The phosphate adsorption isotherm gave good fit adopting Langmuir (r2 = 0.96 to 0.99) and Freundlich (r2= 0.95 to 0.99) for the four soils. Phosphorus sorption maxima was significantly correlated with clay (r2=0.70), Al (r2= 0.73) and Fe (r2=0.81) forms, MPBC (r2=0.67) and Freundlich constants (r2=0.82). Among the various soil properties which correlated with P sorption maxima of significance was clay content (r2=0.97) was significantly correlated. The study illustrated that P sorption isotherm in relation to soil properties can be used as a tool of P management in sustainable crop production.SAARC J. Agri., 14(1): 1-9 (2016)